Health communication: the urgency and challenges of telenursing in remote nursing practice - Yustikasari, Yustikasari; Baharuddin, Tawakkal; Subekti, Priyo; Anisa, Renata; Dewi, Retasari (Jurnal Studi Komunikasi, 2025)
This study examined the challenges and opportunities for telenursing services’ success in remote regions of Indonesia, particularly the role of health communication in addressing these issues. This research was done using Online Research Methods (ORMs) and analysed using NVivo 12 Plus. The results reveal the desperate need to use telenursing to enhance access to and efficiency and quality of services, especially in regions far removed from healthcare facilities. The analysis showed the existence of significant barriers to the care and technological infrastructure of the area, the scant digital literacy among healthcare providers and patients, and fears concerning data security and privacy. Additionally, there is a lack of sufficient government policies and resource funding, which would otherwise improve the situation. To respond to such challenges, this study advocates for adopting other tools such as health communication models, particularly promotional and trust-building therapeutic communication designed for interaction with patients at the clinic, to increase trust and responsiveness among healthcare workers towards telemedicine. Programmatic, regulatory, and institutional documents, schemes, and strategies for digital literacy, public advocacy, and services for training healthcare workers of advanced age are also enabling and essential factors for the practical and sustained application of telenursing in Indonesia.